DYNAMICS OF EMOTIONAL STABILITY IN THE KUTAI'S FAMILY - Handari, Sai (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2020)
This article is based on the results of a mini-research that aims to describe the dynamics of emotional stability in the Kutai's family in East Kalimantan. This research uses the descriptive method with a quantitative approach. The instrument in this study used a questionnaire, then continued with interviews, and observations made to the families of the Kutai tribe in Kabupaten Kutai Kartanegara and Kabupaten Kutai Timur. The data that has been collected is then analyzed using ANOVA quantitative analysis. The results showed that the dynamics of emotional stability in the Kutai's family were not significantly different between the Kutai's family in Kabupaten Kutai Kartanegara and Kabupaten Kutai Timur. The results of this study can be used as a starting material to develop a family counselling and guidance program that focuses on the dynamics of emotional stability in the family, especially in Kutai's family.